The Governance of State Confiscated Goods & State Loot in the Storage House of State Confiscated Goods Class I Yogyakarta - Tuharea, Dyah Ayu Aprilia; Yuska, Syahrial (JURNAL AKTA, 2024)
The protection of property rights in Indonesia is regulated in the 1945 Constitution article 28H paragraph 4. Confiscated goods and state loot confiscated or taken over by the authorities in the investigation process must be stored in the State Confiscated Goods Storage House (RUPBASAN). However, the governance of confiscated goods and loot at the Class I RUPBASAN Yogyakarta faces various problems that require more attention. Problem Formulation from this study What are the problems in the management of confiscated goods and loot in the Class I RUPBASAN Yogyakarta and how the role of the RUPBASAN is in line with the current goals of the Correctional Service. The purpose of this study is to find out and analyze the problems in the governance of confiscated goods and loot in the Class I RUPBASAN Yogyakarta as well as to provide recommendations for improvement and analyze how the role of the RUPBASAN position is in line with the current Correctional Objectives. Methods This research uses a qualitative approach with a descriptive research design of analysis. Data was obtained through in-depth interviews, observations, and document analysis. The results of this study show that several main problems were found in the governance of confiscated goods and confiscated goods in the Class I RUPBASAN Yogyakarta, including limited infrastructure, lack of human resources, and overlapping regulations. The role and position of the RUPBASAN in the Indonesian correctional system shows that although the RUPBASAN is not explicitly regulated in the Indonesian Law No. 22 of 2022 concerning Corrections, the presence of the RUPBASAN still has an important role in supporting the enforcement of human rights and must still be maintained at the Directorate General of Corrections. Recommendations for improvement include increased warehouse capacity, staff training, and clearer and more detailed policy revisions.